GUILLAIN-BARRÃ‰ SYNDROME - Gyang Hanandita Gusti Putri; Nectarine Natasya Regitta Yasmin; Shahdevi Nandar Kurniawan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Guillain-BarrÃ© Syndrome (GBS) is an infection-preceded autoimmune disease attacking myelin sheath of neurons through molecular mimicry, causing neuron demyelination and conduction disruption. GBS is classified into four subtypes: Acute Inflammatory Demyelinating (AIDP), Acute Motor Axonal Neuropathy (AMAN), Acute Motor Sensory Axonal Neuropathy (AMSAN), and Miller Fisher Syndrome. It affects spinal radix which resulted in polyneuropathy, showing mainly symptoms of ascending paresis of the extremity and areflexia. Cerebrospinal fluid evaluation is essential to distinguish GBS from its vast differential diagnosis, with main finding of albuminocytologic dissociation. GBS needs to be managed as fast as possible with intravenous immunoglobulin administration or fresh frozen plasma exchange due to its fast progression.